Wątpliwości dowodowe z podmiotowym kryterium oceny naruszenia prawa do oznaczenia geograficznego. Na przykładzie wyroku TSUE i następczych wyroków sądów niemieckich w sprawie Champagner Sorbet - Trzebiatowski, Marcin (PRAWO i WIĘŹ, 2025)
Designations of origin are also protected when their characteristic ingredient is used in products other than those to which they are directly related. The mere fact that the quantity of the ingredient in such a product complies with the specification of the designation is not sufficient to exclude infringement of the right, particularly in terms of exploiting the designation’s reputation. This is determined by the taste of the product, in which the said ingredient must be clearly perceptible. However, the CJEU judgment in this case, concerning Champagne contained in an ice cream dessert, did not specify precisely whose taste should be used to determine the presence of the essential characteristic of a given designation of origin in the product. This ambiguity, coupled with the additional unavailability of the sorbet on the market, caused the German courts, as national courts implementing the assumptions and guidelines adopted in the aforementioned judgment (and also in the Advocate General’s opinion), to apply a methodology for determining taste that raises serious doubts, particularly in terms of evidence.